Point of care monitoring of oral anticoagulant therapy in children: comparison of CoaguChek Plus and Thrombotest methods with venous international normalised ratio - Ignjatovic, Vera; Barnes, Chris; Newall, Fiona; Hamilton, Simone; Burgess, Janet; Monagle, Paul (Thrombosis and Haemostasis, 2004)
This paper reports the outcome of a research protocol aimed at optimising warfarin monitoring in a tertiary pediatric centre. The Thrombotest™ INR was the standard monitoring test employed to manage oral anticoagulant therapy in children at the Royal Children’s Hospital (RCH), Melbourne. This study compares the results of this standard method to the novel CoaguChek® INR monitor and the “gold standard” technique of venous INR sampling. The objectives were to determine 1) if point-of-care techniques of measuring the INR (Thrombotest and CoaguChek) are accurate and reliable compared to INR results obtained from venous sampling, processed in an accredited laboratory, and 2) if INR results generated by POC devices can be safely used to manage oral anticoagulant therapy in children. 18 children (10 females and 8 males) participated in the study. Ages ranged from 9 months to 21 years (Mean 11.9 years; SD 5.03 years). The agreement between CoaguChek and venous INR measurements (r = 0.885) was shown to be higher compared to Thrombotest and venous INR (r = 0.700). Compared to the venous INR, values obtained with Coaguchek and Thrombotest crossed into or out of the therapeutic range in 25% and 36% of cases respectively. In 88% of the CoaguChek cases and 57% Thrombotest cases, the difference from the venous result was less than 0.5. The CoaguChek method of INR monitoring is a more accurate and reliable method compared to Thrombotest, in the pediatric population tested, and can be safely used to manage oral anticoagulant therapy in children.
Keywords: Anticoagulant monitoring; children; International Normalised Ratio (INR); Point of Care (POC); warfarin